2011
DOI: 10.1029/2010wr009346
|View full text |Cite
|
Sign up to set email alerts
|

An analytical study on stagnation points in nested flow systems in basins with depth‐decaying hydraulic conductivity

Abstract: [1] The existence of stagnation points in nested flow systems is relevant to a range of geologic processes. There has been no analytical study on the characteristics and locations of stagnation points in nested flow systems. We derived analytical solutions for hydraulic head and stream function in basins with isotropic and depth-decaying hydraulic conductivity. The solutions of hydraulic head and stream function are used to identify the positions of stagnation points and discuss the dynamics of groundwater aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
77
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 26 publications
0
77
0
2
Order By: Relevance
“…Analytic and numerical solutions have been derived by assuming that the water table is equal to the topography [e.g., Cardenas, 2007;Craig, 2008;Dahl et al, 2007;Freeze and Witherspoon, 1967;Jiang et al, 2011;Winter, 1978;Zijl, 1999]. These studies have shown the complexity of the nested flow structures, the importance of location of the discharge zones, and the sensitivity of the deep flows given specific water table surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Analytic and numerical solutions have been derived by assuming that the water table is equal to the topography [e.g., Cardenas, 2007;Craig, 2008;Dahl et al, 2007;Freeze and Witherspoon, 1967;Jiang et al, 2011;Winter, 1978;Zijl, 1999]. These studies have shown the complexity of the nested flow structures, the importance of location of the discharge zones, and the sensitivity of the deep flows given specific water table surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[5] In this study, similar to the work by Tóth [1963], Jiang et al [2011], and Zlotnik et al [2011], a steady state Darcian flow in a cross section is investigated. The flow is assumed to be limited below a flat line boundary.…”
Section: Model Descriptionmentioning
confidence: 99%
“…[7] The analytical solutions of topography driven flow in drainage basins for two special cases have been obtained: the case for k x = k z and a = b is given by Jiang et al [2011], and the case for k x ≠ k z and a = b is given by Zlotnik et al [2011]. In this study, a new analytical solution is presented to satisfy more general conditions.…”
Section: Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations